Essays in Anarchism and Religion Volume III - Christoyannopoulos, Alexandre; Adams, Matthew S. (Stockholm Studies in Comparative Religion, 2020)
"Anarchism and religion have historically had an uneasy relationship. Indeed, representatives of both sides have regularly insisted on the fundamental incompatibility of anarchist and religious ideas and practices. Yet, ever since the emergence of anarchism as an intellectual and political movement, a considerable number of religious anarchists have insisted that their religious tradition necessarily implies an anarchist political stance. Reflecting both a rise of interest in anarchist ideas and activism on the one hand, and the revival of religious ideas and movements in the political sphere on the other, this multi-volume collection examines congruities and contestations between the two from a diverse range of academic perspectives. The third volume of Essays in Anarchism & Religion includes five essays focusing on particular individuals - Abraham Heyn, Leo Tolstoy, Herbert Read, Daniel Guérin and Martin Buber - one essay on the affinities between mysticism and anarchism, and one surveying the vast territory of 'spiritual anarchism'. In a world where political ideas increasingly matter once more, and religion is an increasingly visible aspect of global political life, these essays offer scholarly analysis of overlooked activists, ideas and movements, and as such reveal the possibility of a powerful critique of contemporary global society. "